Social Norms–Based Interventions for Risk Driving Behavior in the Upstream Oil and Gas Sector - Pandu Buana Putra; Savitri Citra Budi (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Driving accidents in the upstream oil and gas sector remain an important problem, especially due to overspeeding behavior that contributes from asset damage to fatalities. Although the company has used the In-Vehicle Monitoring System (IVMS), the use of this data has not been optimal as the basis for behavior change interventions. Objective: This study aims to analyze the effectiveness of social norms-based interventions within the framework of the Theory of Planned Behavior (TPB) to reduce risky driving behavior in drivers at PT Onshore XYZ. Methods: The study used a quasi-experimental pretest-posttest control group design involving 42 participants who were divided into an intervention group and a control group. The research instruments include the Driving Behavior Questionnaire (DBQ) and IVMS objective data. The intervention was carried out through the PANDU-K3 program in the form of a social norm feedback poster that displays a comparison of drivers' driving performance. Results: The results showed that the intervention significantly lowered the score of risky driving behavior in the intervention group (p < 0.001) and lowered the average overspeeding offenses from 19.238 to 4.667, or about 75%. Repeated Measures ANOVA analysis showed a significant interaction of time and group (p = 0.004), while the factors of age, working period, and education had no significant effect. Conclusion: These findings imply that IVMS-based social norm interventions are effectively applied as a promotive-preventive strategy to strengthen the culture of driving safety in the oil and gas industry.